Effect of Magnesium Borates on the Fire-Retarding Properties of Zinc Borates - Kipcak, Azmi Seyhun; Acarali, Nil Baran; Derun, Emek Moroydor; Tugrul, Nurcan; Piskin, Sabriye (HINDAWI LTD, 2014)
Magnesium borate (MB) is a technical ceramic exhibiting high heat resistance, corrosion resistance, great mechanical strength, great insulation properties, lightweightness, high strength, and a high coefficient of elasticity. Zinc borate (ZB) can be used as a multifunctional synergistic additive in addition to flame retardant additives in polymers. In this study, the raw materials of zinc oxide (ZnO), magnesium oxide (MgO), and boric acid (H3BO3) were used in the mole ratio of 1:1:9, which was obtained from preexperiments. Using the starting materials, hydrothermal synthesis was applied, and characterisation of the products was performed using X-Ray diffraction (XRD) and Fourier transform infrared (FT-IR) and Raman spectroscopies. The forms of Zn3B6O12 center dot 3.5H(2)O, MgO(B2O3)(3)center dot 7(H2O),and Mg-2(B6O7(OH)(6))(2)center dot 9(H2O)were synthesised successfully. Moreover, the surface morphology was investigated using scanning electron microscopy (SEM), and the B2O3 content was determined. In addition, the reaction yields were calculated. The results of the B2O3 content analysis were in compliance with the literature values. Examination of the SEM images indicated that the obtained nanoscale minerals had a reaction efficiency ranging between 63-74% for MB and 87-98% for ZB. Finally, the fire-retarding properties of the synthesised pure MBs, pure ZBs, and mixtures of MB and ZB were determined using differential thermal analysis and thermal gravimetry (DTA-TG) and differential scanning calorimetry (DSC).
Keywords: Chemistry